TUGAS DAN TANGGUNGJAWAB GURU SEKOLAH MINGGU TERHADAP MASA DEPAN GEREJA - Hasudungan Simatupang (Institut Agama Kristen Negeri Tarutung, 2020)
The purpose of this study was to determine the role of Sunday school teachers in organizing a series of learning processes not just the responsibility of filling free time on Sundays. This type of research is qualitative, using devotional theological research methods trying to apply the meaning of discourse to the reader's personal life without being separated from the learning objectives. The results of this qualitative research show the role of Sunday school teachers in preparing the ecclesiastical generation through the learning process as an effort to foster a generation of Christian churches from an early age. The tendency to use the learning method used, namely participatory fun, is very suitable for children, it can be followed through prayer, spiritual chanting, alphabeticism, followed by psychomotor (physical) movements in interpreting the discourse of a number of previously set learning objectives. The children were very loved by God, and the children showed enthusiasm to praise God, they were very excited in a cheerful atmosphere following the fun learning process. Thus it can be concluded how important the role of Sunday school teachers is to prepare the Christian church generation from an early age according to God's will.BAHASA INDONESIA ABSTRACT: Tujuan penelitian ini untuk mengetahui peran guru Sekolah Minggu menyelenggarakan serangkaian proses pembelajaran tidak sekedar tanggung jawab mengisi waktu senggang pada hari minggu Jenis penelitian ini kualitatif, menggunakan metode penelitian teologis devosional berusaha menerapkan makna wacana pada kehidupan pribadi pembaca tanpa dapat dipisahkan dari tujuan pembelajaran. Hasil penelitian kualitatif ini memperlihatkan peran guru Sekolah Minggu mempersiapkan generasi gerejawi melalui proses pembelajaran sebagai upaya pembinaan generasi gereja Kristen sejak dini. Kecenderungan pemanfaatan metode pembelajaran yang digunakan yakni partisipatif menyenangkan sangat cocok bagi anak-anak, dapat diikuti melalui doa, nyanian rohani, mengabjad, diikuti gerakan-gerakan psikomotorik (fisik) dalam memaknai wacana sejumlah tujuan pembelajaran yang ditetapkan sebelumnya. Anak-anak sangat disayangi Tuhan, dan anak-anak menunjukkan antusiasme memuji Tuhan sangat bergelora dalam suasana riang gempita mengkuti proses pembelajaran menyenangkan. Dengan demikian disimpulkan betapa pentingnya peran guru sekolah minggu mempersiapkan generasi gereja Kristen sejak dini sesuai kehendak Tuhan.